Customer Equity Building in Multilevel Marketing Firms: An exploratory Study in the Malaysian Direct Selling Industry - Ho, Yin Shan (2007)
In a rapidly changing technological environment, products come and go, but customers remain; the long-term value of a company is greatly determined by the value of company's customer relationships (Rust, Zeithaml & Lemon, 2000). This has much truth in MLM businesses since such firms count on its customers to transform social networks into marketing distribution apportunities. The major challenge confronting such organisations is to offer their customers with good reasons to invest in their company.To reach the desired outcome, a richer understanding on the customers’ end is highly demanded. However, in-depth research in this branch of direct selling has often been ignored due to various scepticisms, and scholarly articles related to this field are meagre. In this study, the Malaysian consumers’ perception towards MLM has been examined. Besides that, the determinants of customer equity of MLM businesses based in Malaysia have also been explored. The results of the survey are quite encouraging. Responses indicate that Malaysian consumers had a moderately positive view towards MLM. The findings of the research supports the proposition that various factors of customer personal profile (economic motive, social tie, past experience), marketing mix product, price, place, plan), organisational feature company standing, buyback protection, training, sales team behaviour) and industry characteristic (public image) are important predictors of customer equity that determine the MLM industry. However, different set of predictors are significant in different attainment of customer equity. So, partakers in the industry could strategies accordingly in the respective areas to maximise their customer equity.